KOMUNIKASI TERAPEUTIK PERAWAT PADA PASIEN KANKER DI RSUD PANEMBAHAN SENOPATI BANTUL YOGYAKARTA - Lailli Sofianingtyas; Wenny Savitri; Masta Hutasoit (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: Therapeutic communication is communication that facilitates recovery of the patient and it is a kind of planned communication. Therapeutic communication also becomes a good instrument to build relationship between health staff and patient. Besides physical problem, the cancer patients have to face psychological problem due to their illness. Therefore, as medical staff who continuously by site of with the patients in hospital, their capability for therapeutic communication is absolutely required. Objective: To get an overview of therapeutic communication of nurses with cancer patients at Panembahan Senopati Hospital Bantul Yogyakarta. Method: The studi used descriptive observation design and total sampling techniques. There were 26 respondents, i.e. nurses working at Nusa Indah 2 and Melati Ward of Panembahan Senopati Hospital Bantul Yogyakarta. Data were obtained through checklist observation guide and analyzed using percentage formula. Result: Therapeutic communication of nurses at orientation phase was adequate (84.6%), at work phase was adequate (92.3%), at termination phase was adequate (73.1%). All of the nurse therapeutic communication phases were majority adequate (92,3%). Conclusion: Therapeutic communication of the nurses at Panembahan Senopati Hospital Bantul Yogyakarta belonged to adequate category. The result of the studi suggested that the practice of therapeutic communication be improved. Training on therapeutic communication should be conducted periodically. Keywords: Therapeutic communication, cancer patients